Quantification of circadian rhythm in mitochondrial DNA copy number in whole blood, and identification of factors that influence it - Wang, Yakun; Liu, Yuanwu; Zhao, Yiqiang; Luo, Junjie (Cellular and Molecular Biology, 2020)
Mitochondrial DNA (mtDNA), the genetic material in mitochondria, encodes key genes related to the respiratory chain and ATP production. To accurate quantification mtDNA content in whole blood is important for various disease states. Absolute quantitative Real-time PCR and platelet contamination erase method were used for mtDNA copy number analysis in whole blood. In the quantitative study of mtDNA content, it was found that whole blood mtDNA copy number showed a fluctuating rhythm during a 24-h period due to dynamic changes in white blood cells combined with platelets. However, when isolated white blood cells were used, or absolute whole blood mtDNA was calculated, the circadian rhythm pattern of mtDNA disappeared. In this study, a feasible method that can accurately quantify mitochondrial DNA in small blood samples was established, and it was found that two factors which greatly influenced mtDNA copy number were sampling time and platelets in blood.